2008
DOI: 10.1051/gse:2008028
|View full text |Cite
|
Sign up to set email alerts
|

Further insights of the variance component method for detecting QTL in livestock and aquacultural species: relaxing the assumption of additive effects

Abstract: -Complex traits may show some degree of dominance at the gene level that may influence the statistical power of simple models, i.e. assuming only additive effects to detect quantitative trait loci (QTL) using the variance component method. Little has been published on this topic even in species where relatively large family sizes can be obtained, such as poultry, pigs, and aquacultural species. This is important, when the idea is to select regions likely to be harbouring dominant QTL or in marker assisted sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2009
2009
2009
2009

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 23 publications
(12 reference statements)
1
3
0
Order By: Relevance
“…We expect, however, that major genes having moderate dominance effects will be detected with the simpler additive version of FIA. These results are similar to the ones obtained by Martinez [ 9 ] where he showed that the power of VC-based models does not increase substantially by including dominance effects as long as the QTL effects are not overdominant. The difference in power for HK-regression with or without dominance included in the model seem to be small as long as the QTL effects are not overdominant.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…We expect, however, that major genes having moderate dominance effects will be detected with the simpler additive version of FIA. These results are similar to the ones obtained by Martinez [ 9 ] where he showed that the power of VC-based models does not increase substantially by including dominance effects as long as the QTL effects are not overdominant. The difference in power for HK-regression with or without dominance included in the model seem to be small as long as the QTL effects are not overdominant.…”
Section: Resultssupporting
confidence: 90%
“…Hence, for a single QTL model there is no covariance between additive and dominance effects. The estimates of and may be strongly correlated, however, since the IBD-values in Π and Δ are correlated [ 9 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations